AB0023 Sex-based differences in association between circulating t cell subsets and disease activity in untreated early rheumatoid arthritis patients. (12th June 2018) - Aldridge, J.; Pandya, J.; Meurs, L.; Kerstin, A.; Nordström, I.; Theander, E.; Lundell, A.-C.; Rudin, A.
Abstract : Background: Genetic association studies strongly support the role of CD4 + T cells in promoting RA pathology. In a cohort of untreated early RA patients, we recently demonstrated that the balance of helper T cell subsets in blood of ueRA patients is skewed towards Th2 cells relative to healthy controls. 1 RA has been shown to be a sexually dimorphic condition with current data suggesting that prevalence, disease course and treatment outcome varies between men and women. Objectives: It is not known if sex-based disparities in immunological factors contribute to the disease process in rheumatoid arthritis (RA). Hence, we examined whether circulating T cell subset proportions and their association with disease activity differed in male and female patients with untreated early rheumatoid arthritis. Methods: Proportions of T cell subsets were analysed in peripheral blood from 70 ueRA DMARD and prednisolone naïve patients with untreated early Rheumatoid arthritis (50 females and 20 males) and in 31 healthy age-matched controls. Broad analysis of helper and regulatory CD4 + T cell subsets was done using flow cytometry. Disease activity in patients was assessed using DAS28, CDAI, swollen joint counts, tender joint counts, CRP and ESR. Results: Multivariate factor analyses showed that male and female untreated early rheumatoid arthritis patients display distinct profiles of association between disease activity and circulating T cell subset proportions. In male, but not female, ueRA patients Th2 cells showed a positive association with disease activity and correlated significantly with DAS28-ESR, CDAI and tender joint counts. Likewise, proportions of non-regulatory CTLA-4 + T cells associated positively with disease activity in male patients only, and correlated with DAS28-ESR. In contrast, there was a negative relation between Th1Th17 subset proportions and disease activity in males only. Proportions of Th1 and Th17 cells showed no relation to disease activity in either males or females. There were no significant differences in proportions of T cell subsets between the sexes in patients with untreated early rheumatoid arthritis. Conclusions: In conclusion, our findings show sex-based differences in the association between T cell subsets and disease activity in ueRA patients, and that Th2 helper T cells may have a stronger role in the regulation of disease activity in male patients. Reference: [1] Pandya JM, et al. Circulating T helper and T regulatory subsets in untreated early rheumatoid arthritis and healthy control subjects. J Leukoc Biol2016;100(4):823–833. Disclosure of Interest: J. Aldridge: None declared, J. Pandya: None declared, L. Meurs: None declared, A. Kerstin: None declared, I. Nordström: None declared, E. Theander Employee of: Janssen Cilag, A.-C. Lundell: None declared, A. Rudin Consultant for: AstraZeneca